THE EFFECTIVENESS OF SELF-MANAGEMENT TECHNIQUE GROUP COUNSELING IN REDUCING TRUANCY AMONG HIGH SCHOOL STUDENTS - Usnul Cholifah; Ratih Christiana; Asroful Kadafi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to examine the effectiveness of group counseling using the self-management technique in reducing truancy behavior among tenth-grade students at SMA Negeri 1 Patianrowo. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample was selected through purposive sampling and involved 17 tenth-grade students identified as having high levels of truancy behavior, who were divided into an experimental group (n = 8) and a control group (n = 9). Data on truancy behavior were collected using a questionnaire and analyzed using non-parametric statistical tests, namely the Wilcoxon Signed Ranks Test and the Mann–Whitney U Test. The results of the Wilcoxon test in the experimental group showed a significant difference between pre-test and post-test scores, with an Asymp. Sig. (2-tailed) value of 0.005 (p < 0.05), indicating a substantial reduction in truancy behavior after the implementation of group counseling with the self-management technique. In contrast, the control group did not demonstrate a significant change. Furthermore, the Mann–Whitney U test on post-test scores revealed an Asymp. Sig. (2-tailed) value of 0.001 (p < 0.05), confirming a statistically significant difference between the experimental and control groups.The novelty of this study lies in the integration of the “7 Kebiasaan Anak Indonesia Hebat” (Seven Habits of Great Indonesian Children) into the implementation of group counseling with the self-management technique, including habits such as waking up early, religious observance, regular physical exercise, learning enthusiasm, and going to bed early as supporting strategies for fostering students’ disciplinary behavior. Based on these findings, it can be concluded that group counseling using the self-management technique is significantly effective in reducing truancy behavior among tenth-grade students at SMA Negeri 1 Patianrowo.